Uniwersytet i pracodawcy w Polsce i Hiszpanii. Konfrontacje, oczekiwania, perspektywy - Kurantowicz, Ewa; Nizińska, Adrianna; Padilla-Carmona, Teresa; González-Monteagudo, José (Studia Edukacyjne, 2017)
This paper is based on the partial results of EMPLOY research project. We present the Polish and Spanish employers’ perspectives, experiences and needs when it comes to the HE graduates. Before the empirical analyses we compare the political and cultural contexts of employability in both countries as also provide the review of the main Polish and Spanish research reports in this field.